Unmasking Advanced HIV Infection: A Case of Refractory Thrombocytopenia Misdiagnosed as Immune Thrombocytopenic Purpura - Wiratama Hadi Tjuanda; Anak Agung Ayu Yuli Gayatri (HM Publisher, 2025)
Thrombocytopenia is a frequent hematological abnormality in individuals with human immunodeficiency virus (HIV) infection and can be the initial presenting sign. Its clinical picture can closely mimic primary Immune Thrombocytopenic Purpura (ITP), leading to diagnostic delays and inappropriate management. This report highlights a case where an HIV diagnosis was revealed during the workup for refractory thrombocytopenia. A 39-year-old female presented with fatigue and gingival bleeding. She had a previous diagnosis of ITP and had been treated intermittently, but the thrombocytopenia repeatedly recurred. Physical examination was notable for oral candidiasis. Laboratory investigations confirmed severe thrombocytopenia with a platelet count of 4,000/µL. Subsequent serological testing was reactive for HIV, with a CD4 count of 136 cells/µL. The patient was managed for severe thrombocytopenia and opportunistic infection, with a plan to initiate antiretroviral therapy. In conclusion, this case underscores the critical importance of including HIV infection in the differential diagnosis for patients presenting with new-onset or refractory thrombocytopenia. Clinical clues, such as opportunistic infections, should prompt immediate HIV screening to ensure timely diagnosis and initiation of definitive therapy, thereby preventing misdiagnosis and improving patient outcomes.